Cortisol awake response imbalance as an indicator of acute central serous chorioretinopathy: Relationship with choriocapillaris and choroidal features - Scarinci, Fabio; Patacchioli, Francesca Romana; Costanzo, Eliana; Parravano, Mariacristina (Frontiers in Medicine, 2022)
Purpose The purpose of the present study was to measure in central serous chorioretinopathy (CSC) the salivary cortisol awake response (CAR) delta percentage (Δ%) variation, a distinct and robust indicator of cortisol rhythm during wakefulness, commonly proposed as a marker of hypothalamic-pituitary adrenal (HPA) axis activity, whose alteration is frequently associated with several adverse health outcomes. Methods In the present cross-sectional observational study, salivary CAR Δ% variation was assessed in 17 adult male subjects affected by acute naïve CSC and compared to 17 matched healthy controls. Choroid vasculature metrics were assessed in the study population by measuring the subfoveal choroidal thickness (FCT) and the choroidal vascularity index (CVI) by the imaging technique of enhanced-depth imaging spectral-domain optical coherence tomography (EDI-SD-OCT). Furthermore, flow signal void area features of the choriocapillaris were evaluated in the study population using OCT angiography (OCTA). Results Both the control and CSC groups showed a physiological cortisol increase that occurred during the first 30 min after awaking. However, CSC adult male patients showed remarkably blunted CAR Δ% variation in comparison with controls, which might reflect a CSC-related imbalance of HPA axis activity. Statistically significant correlations were shown by Pearson’s correlation test between salivary CAR Δ% and the selected choroidal and choriocapillaris imaging biomarkers (FCT, CVI, and flow signal void area) in the study population. Conclusion In conclusion, alterations of the CAR Δ% increase, associated with choroidal-retinal metrics, might provide a window into the physiopathology of acute CSC, suggesting a possible common factor to explain the association between stress and CSC.